Experienced and novice EFL teachers beliefs regarding feedback : a case study. (2021)
The present research follows a qualitative approach and it is a representative case study with 6 participants. It aims to answer to the question: How do experienced and novice EFL teachers from the UPN acknowledge feedback taking into account the different levels of education in Colombia? First, data revealed that teachers tend to focus on productive skills when giving their opinions about feedback. Also, the participants define feedback as a tool that allows students to improve and that can be used to raise consciousness about their learning. Further, data showed the lack of access and knowledge to the official documents and the absence of guidelines that frame feedback delivery for teachers, stating the necessity to spread and create spaces for this matter in educational scenarios.